Effects of emerging persistent organic pollutant perfluorooctane sulfonate (PFOS) on the Crustacean Gammarus insensibilis. Issue 8 (17th November 2019) - Touaylia, Samir; Khazri, Abdelhafidh; Mezni, Ali; Bejaoui, Mustapha
Abstract: Perfluoroalkyls are stable synthetic chemicals, used in the manufacturing of various industrial products. The release of these compounds in natural ecosystems could interact with living organisms leading to sea food species modification. Laboratory experiments were performed to assess its toxicity on the marine invertebrate Gammarus insensibilis. The LC50 determined by the Regtox package considering several concentrations (5, 10, 15, and 20 mg/L) was about 9.99 mg/L. The biomarkers response was analyzed using adult crustacean treated with 1, 1.6, and 3.1 mg/L of PFOS for 4 days. At the end of the exposure, the activities of acetylcholinesterase (AChE) and superoxyde dismutase (SOD) as well as the malondialdehyde rate (MDA) were measured. The SOD activity was increased at low concentration of PFOS, in contract to the highest one, where it decreased. The AChE activity remains relatively unchangeable during exposure to the tested concentrations, indicating that PFOS is not neurotoxic. The rate of MDA increased after exposure to 1 mg/L of PFOS, which reveals a possible membranous deterioration. The results indicated that oxidative stress and cell damage might be one of the main mechanisms of PFOS toxicity to organisms.